Konflik Keluarga dalam Novel Lebih Senyap Dari Bisikan karya Andina Dwifatma - Aldifa, Zaky Naufal; Zulfadhli (Universitas Negeri Padang, 2024)
This research aims to describe the form of family conflict, describe the causes of family conflict, and describe the impact of family conflict in the novel Lebih Senyap dari Bisikan by Andina Dwifatma. The data source of this research is the novel Lebih Senyap dari Bisikan by Andina Dwifatma. This type of research is literary research and the method used in this research is descriptive method. The results of this study are classified as follows (1) family conflict forms are found, namely husband and wife conflict and child conflict with parents, (2) family conflict causes are found from personality immaturity; the presence of incompatible personality traits; mental abnormalities; finance or economy; household chores; childcare; and interaction within the family, (3) and the impact of family conflict is found, namely mental health; physical health; and family health.